2008
DOI: 10.1021/ef800236y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of the Effects of Gasoline Blends on Single-Cylinder Diesel Engine Performance and Exhaust Emissions

Abstract: The present study investigates experimentally and theoretically the effects of using of gasoline-diesel fuel blends on single-cylinder diesel engine performance and exhaust emissions. The study consists of two parts: (i) Experimental study: The effects of using of different gasoline-diesel fuel blends have been investigated experimentally and compared in a single-cylinder diesel engine. In this part, the effects of 2-10% gasoline blends have been investigated experimentally in a single-cylinder diesel engine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
8
0
3
Order By: Relevance
“…Yani bu durumda benzin karışımı ile tutuşma gecikmesinin arttığı söylenebilir. Literatürde de benzeri sonuçlar bulunmuştur [6][7][8][9]. Ayrıca söz konusu şekilden benzin karışımları ile açığa çıkan ısı miktarının arttığı da görülebilir.…”
Section: Bdyk'larının Silindir Basıncı Sıcaklığı Ve Açığa çıKan Isı unclassified
See 2 more Smart Citations
“…Yani bu durumda benzin karışımı ile tutuşma gecikmesinin arttığı söylenebilir. Literatürde de benzeri sonuçlar bulunmuştur [6][7][8][9]. Ayrıca söz konusu şekilden benzin karışımları ile açığa çıkan ısı miktarının arttığı da görülebilir.…”
Section: Bdyk'larının Silindir Basıncı Sıcaklığı Ve Açığa çıKan Isı unclassified
“…Bununla birlikte; benzin, fumigasyon ve karışım gibi iki farklı yöntemle dizel motorlarında da kullanılabilmektedir ve söz konusu yöntemlerin uygulanması ile motor performans parametrelerinin iyileştiği ve çevre kirliliğinin azaldığı belirlenmiştir [4][5][6][7][8][9]. Benzinin emme kanalında emme havasının içerisine püskürtüldüğü fumigasyon yöntemi ile ilgili Durgun ve Şahin tarafından hem deneysel ve hem de sayısal çalışmalar yapılmıştır [2,4,5].…”
Section: Gi̇ri̇ş (Introduction)unclassified
See 1 more Smart Citation
“…Han et al [6] carried out series researches on the combustion and emissions characteristics of a single-cylinder diesel engine using the Diesel-Gasoline Blend Fuel, their research results showed that by employing a proper ratio of diesel to gasoline, the operation range of HCCI engine could be greatly broadened, meanwhile a lower emission level could be achieved. A reduced gas-phase chemical mechanism of "dieseline" was developed by Kokjohn et al [7] , then the mechanism was coupled with the KIVA code to establish the "dieseline" HCCI mode, based on this mode, lots of simulation works about the combustion and emissions characteristics of the "dieseline" engine had been done [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [6] carried out series researches on the combustion and emissions characteristics of a single-cylinder diesel engine using the Diesel-Gasoline Blend Fuel, their research results showed that by employing a proper ratio of diesel to gasoline, the operation range of HCCI engine could be greatly broadened, meanwhile a lower emission level could be achieved. A reduced gas-phase chemical mechanism of "dieseline" was developed by Kokjohn et al [7] , then the mechanism was coupled with the KIVA code to establish the "dieseline" HCCI mode, based on this mode, lots of simulation works about the combustion and emissions characteristics of the "dieseline" engine had been done [8][9][10] .In general, combustion and emission characteristics of ICE are greatly affected by the atomization of fuel sprays. In turn, fuel atomization and evaporation are strongly influenced by fuel properties such as density, surface tension, viscosity et al "Dieseline" is a new blend fuel, research works on its physical properties have rarely been done or published yet, thus it is of significance to establish the database of physical parameters of this new blend fuel.…”
mentioning
confidence: 99%